Family Communication Patterns as a Determinant of Learners’ Academic Performance in Selected Schools in Baringo North Sub-County, Kenya - Elizabeth Jepkorir Kiptoo; John Kiptanui Kitur; Mercy Muthiga Mauki (ShahidiHub International Journal of Education, Humanities & Social Science, 2026)
This paper explores the contribution of the family communication patterns to learners’ academic performance in selected schools in Baringo North Sub-County, Kenya. A mixed-methods approach was employed, with qualitative and quantitative data gathered through questionnaires, the Family Resilience Assessment Scale, and Interviews. Purposive sampling was used to select the schools that participated in the study based on their performance and their category: County-level schools. The sample comprised 363 students, 50 teachers, and 5 parent representatives. The results revealed a strong, statistically significant effect of family communication on academic performance (β = 0.453; p < 0.05). The study concludes that children’s learning behavior is greatly impacted by the values they are taught at home. In particular, learners who value respect can apply it at school, thereby improving their academic achievement. In addition, values instill in students the courage to approach teachers, the confidence to ask questions, and the ability to engage in class, all of which facilitate learning. Second, active family involvement in school activities is one of the major elements impacting students’ academic success. Learners’ performance is influenced by the family’s ability to cope with and adjust to changes. Parents must recognize and prioritize the value of their role in their children’s education and support their needs. Finally, Students’ academic performance can be enhanced by parents and teachers communicating openly and efficiently. The study recommends that parents and guardians have a fundamental responsibility to teach their children the moral values and social skills required for lifelong learning. Second, families and communities establish routines for children and create a positive learning environment. This will help students cultivate a disciplined approach to learning. Effective communication between parents and schools requires active listening, transparency, and trust.